2019
DOI: 10.3847/1538-4357/aaeed4
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR and Keck Observations of Heavily Obscured Quasars Selected by WISE

Abstract: A primary aim of the N uclear Spectroscopic T elescope Array (NuSTAR) mission is to find and characterize heavily obscured Active Galactic Nuclei (AGNs). Based on mid-infrared photometry from the Wide-Field Infrared Survey Explorer (WISE ) and optical photometry from the Sloan Digital Sky Surveys, we have selected a large population of luminous obscured AGN (i.e., "obscured quasars").Here we report NuSTAR observations of four WISE -selected heavily obscured quasars for which we have optical spectroscopy from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 112 publications
2
28
0
Order By: Relevance
“…This value is comparable to that found in W0204-0506, while those found in W0116-0505 and W0220+0137 are lower. Unfortunately the large uncertainties in this quantity make this result difficult to interpret, but it is worth noting that recently Yan et al (2019) identified a very low dust-to-gas ratio of ≈4×10 −25 cm 2 for a heavily obscured nearby quasar at z=0.218 with N H ≈3× 10 25 cm −2 , with around N H ≈10 23 cm −2 coming from the ISM, which could be a better analog to our objects. If the dustto-gas ratio is indeed significantly lower in W0116-0505 and W0220+0137 than in W0204-0506, it could either imply a low metallicity for the former systems such that there is a deficit of dust overall in the host galaxy, or that a higher than typical fraction of absorbing gas exists within the dust sublimation radius of the accretion disk.…”
Section: X-ray Data Modelingmentioning
confidence: 73%
“…This value is comparable to that found in W0204-0506, while those found in W0116-0505 and W0220+0137 are lower. Unfortunately the large uncertainties in this quantity make this result difficult to interpret, but it is worth noting that recently Yan et al (2019) identified a very low dust-to-gas ratio of ≈4×10 −25 cm 2 for a heavily obscured nearby quasar at z=0.218 with N H ≈3× 10 25 cm −2 , with around N H ≈10 23 cm −2 coming from the ISM, which could be a better analog to our objects. If the dustto-gas ratio is indeed significantly lower in W0116-0505 and W0220+0137 than in W0204-0506, it could either imply a low metallicity for the former systems such that there is a deficit of dust overall in the host galaxy, or that a higher than typical fraction of absorbing gas exists within the dust sublimation radius of the accretion disk.…”
Section: X-ray Data Modelingmentioning
confidence: 73%
“…Our models need to be able to recover the following observational constraints: (1) the host M halo for our simulated obscured and unobscured quasars, as well as (2) Yan et al 2019). We note that we adopt such a broad observed obscured fraction to reflect the uncertainty due to the difficulty of detecting heavily-obscured AGN.…”
Section: Resultsmentioning
confidence: 99%
“…Using relationships between host galaxy gas content and stellar mass as presented in and Pannella et al (2009), it was also possible to model quasar obscuration as a function of its host galaxy's stellar mass. We find that although some of these models were able to produce host M halo that fell within the range of clustering measurements, they are not viable since the obscured fractions for these populations were outside the observed range (e.g., Treister et al 2008;Polletta et al 2008;DiPompeo et al 2016b;Yan et al 2019). We also considered the effect of allowing our simulated quasars to be obscured by the parsec-scale dusty torus and by its host galaxy's interstellar gas.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the expected upper-bound reaches to log(L 2−10 /erg s −1 ) = 42.92, or log(L bol /erg s −1 ) = 44.22, exceeding the upper-bound obtained from the Spitzer /IRS spectra. However, this situation is unlikely because the reprocessed infrared emission should be observed even in such highly obscured situation, contributing to the Spitzer /IRS spectra (e.g., Yan et al 2019). Thus, we conclude that the central engine of Arp 187 is likely to be dead, even if we consider the Compton-thick level obscuration, but the extreme absorption reaching N H = 10 25 cm −2 is also unlikely.…”
Section: Very Faint Agn Even If It Is Highly Obscuredmentioning
confidence: 99%